On the Mystery of Financial Conservatism: Insights from Pakistan. Issue 12 (26th September 2019) - Yasmin, Ammara; Rashid, Abdul
ABSTRACT: This article empirically explores the prevalence and determinants of financial conservatism at Pakistani nonfinancial firms during the period 1998–2014. Along with several firm-specific variables as predictors of the most prominent theories, the effects of macroeconomic conditions and business group affiliation are also investigated. The results of the study show that approximately 14% of the firm-year observations are financially conservative. The ratio of financial conservatism almost doubled over that period, from 11.25% in 1999 to 20.76% in 2014. We find that financially conservative firms are more profitable, less risky, and pay higher dividends than their non-conservative counterparts. The results of the logistic regression reveal that the financial hierarchy and financial flexibility are the most powerful motives for avoiding debt financing. Finally, we show that macroeconomic conditions and business group affiliation also play a significant role in determining the likelihood of financial conservatism.